THE USE OF MOULAGE IN CLINICAL SIMULATION: MULTIPLE CASE STUDIES (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: identify how and why to use moulage within clinical simulation practices. Method: it is a multiple, inclusive, descriptive and exploratory case study with a qualitative approach. The cases were selected through an intentional sample. After applying the eligibility criteria, four cases of simulated scenarios that used moulage were included and analyzed. Results: all the cases analyzed were developed in extracurricular simulated clinical activities by facilitators with experience in clinical practices, teaching and simulation. The moulages used differenttechniques, promoting greater interaction with the learner through the use of stimulants of different sense organs, sharpening clinical reasoning, the development of skills, competences, among others. In the four cases, the moulage was performed on a simulated patient, in simulated scenarios and simulated video. The reasons described for moulage were: to provide realism, fidelity, easy application and low cost. Conclusion: it was possibleto identify that the moulage is an adequate resource in clinical simulation and that when built with rigor and method, it influences the fidelity and realism of the simulated scenario.